Determination of spatial proximity between the N-terminus and cocaine binding site of the dopamine transporter by FrEt - (:unkn) unknown (My University, 2015)
Amaç: Dopamin taşıyıcılar (DAT) dopaminin sinaptik gerialımından ve böylelikle sinirsel iletinin çabuk sonlanmasından sorumludur. Bu proteinler alışkanlık yapıcı kokain, amfetamin gibi maddelerin de etki merkezlerini oluşturur. Proteinin N-ucunda bulunan Serin 7 ve 12'nin fosforilasyon bakımından kritik amino asitler olduğu bilinmektedir. Bu çalışmada N-ucu ile kokain bağlama bölgesi arasındaki uzaklık, yaban tip ve Ser7/12Asp ve Ser7/12Ala mutantlarında belirlenmiştir.Gereç ve Yöntem: Sarı-floresan protein (YFP) ve mutasyonlar DAT'ın N-terminal ucuna 2-aşamalı PCR ile yerleştirilmiştir. Dopamin geri-alım testleri yapılmış ve konfokal mikroskopta verici-ağartma yöntemi ile Förster rezonans enerji transferi (FRET) mesafeleri belirlenmiştir. bulgular: Tüm N-ucundan YFP-etiketlenmiş DAT proteinleri düzgün olarak hücre yüzeyine taşınmıştır. K değerleri sırasıyla yaban tip, Ser7/12Ala and Ser7/12/Asp mutantları için 0.76, 0.75 ve 1.24 mM olarak saptanmıştır. FRET etkinliği yaban-tip DAT için 0.15 olarak bulunmuş ve FRET uzaklığı 68.4 Å olarak bulunmuştur. Diğer konstraktlarda FRET etkinlikleri negatiftir ve enerji transferi saptanmamıştır.

Objective: The dopamine transporter (DAT) mediates uptake of dopamine from the synaptic cleft and provides rapid termination of neurotransmission. It is the site of action for different drugs of abuse, including cocaine and amphetamine. Serine 7 and 12 at the N-terminus were found to be critical residues in phosphorylation. Here, we addressed spatial proximity site relationship of N-terminal extension with respect to cocaine binding in wild type and Ser7/12Asp and Ser7/12Ala mutants. Materials and Methods: The yellow-fluorescent protein (YFP) and mutations were introduced into the N-terminus of the hSynDAT by a two-step PCR. Dopamine uptake assays were performed and Förster resonance energy transfer (FRET) distances were determined using donor bleach method in a confocal microscope.results: All N-terminally YFP-tagged DAT constructs were properly trafficked to the cell surface. K values were 0.76, 0.75 and 1.24 mM for wild-type, Ser7/12Ala and Ser7/12/Asp constructs, respectively. FRET efficiency value was found to be 0.15 for YFP-labeled DAT while corresponding estimated distance was calculated as 68.4 Å. FRET efficiencies of other constructs were negative and no energy transfer was detected.
Dopamin taşıyıcıların kokain bağlama bölgesi ile N-ucu arasındaki uzaysal yakınlığının FRET ile belirlenmesi
Keywords: Genel ve Dahili Tıp